Intravascular Large B-cell Lymphoma: A Report of Two Cases - Fereshteh Ameli; Fatemeh Nili; Hana Saffar (Iranian Society of Pathology, 2020)
One of the rare variants of extranodal large B-cell lymphoma is intravascular large B-cell lymphoma (IVLBCL). Characteristics of IVLBCL include intraluminal selective proliferation of atypical lymphoid cells in small to medium-sized vessels. The etiologic of IVLBCL is unknown, but due to the growth pattern of this tumor, it is speculated that IVLBCL is caused by a defect in homing receptor of tumor cells. IVLBCL can involve any organ but central nervous system, lungs, and skin are the most involved sites. IVLBCL does not usually involve lymph nodes. IVLBCL mainly occurs in the middle aged to elderly population with a slight male predominance. Generally, IVLBCL is aggressive and rapidly fatal if left untreated. We here reported two cases of IVLBCL who succumbed to the disease at initial phase of treatment to emphasize the difficulty in diagnosis of IVLBCL due to its exclusive intravascular growth pattern and fulminant clinical course.